2013
DOI: 10.3109/02770903.2013.799688
|View full text |Cite
|
Sign up to set email alerts
|

AsthmaWise – a field of dreams? The results of an online education program targeting older adults with asthma

Abstract: Objectives: The aim of this study was to establish the feasibility and acceptability of an online asthma selfmanagement program developed for older Australians with asthma. Methods: AsthmaWise, an internet education self-management program, was piloted for a 3-month period at the beginning of 2012. Participants were recruited using both online and offline strategies and were required to complete surveys, both pre-and post-intervention, in a repeated measures design. Results: Matched data were collected from 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 49 publications
0
46
0
Order By: Relevance
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Only the two pre-post studies [62,63] reported a significant effect of the intervention on asthma control.…”
Section: Asthma Controlmentioning
confidence: 99%
See 3 more Smart Citations